2021
DOI: 10.1096/fj.202001782rr
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of IL33 signaling in negative pregnancy outcomes associated with lipopolysaccharide exposure

Abstract: Interleukin 33 (IL33) signaling has been implicated in the establishment and maintenance of pregnancy and in pregnancy disorders. The goal of this project was to evaluate the role of IL33 signaling in rat pregnancy. The rat possesses hemochorial placentation with deep intrauterine trophoblast invasion; features also characteristic of human placentation. We generated and characterized a germline mutant rat model for IL33 using CRISPR/Cas9 genome editing. IL33 deficient rats exhibited deficits in lung responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 89 publications
0
7
1
Order By: Relevance
“…Finally, although prior work had shown that IL-33 contributes to protection against LPS-induced complications and preterm labor at late gestation in mice and rats ( 17 , 18 ), we now demonstrate that IL-33 acts very early in pregnancy to critically regulate the tissue and vascular remodeling processes that establish the foundation for proper development and function of the placenta. This early role for IL-33 could impact, and possibly explain, some of the complications that arise at later stages of pregnancy in LPS-challenged rodents and in women with diverse pregnancy disorders.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…Finally, although prior work had shown that IL-33 contributes to protection against LPS-induced complications and preterm labor at late gestation in mice and rats ( 17 , 18 ), we now demonstrate that IL-33 acts very early in pregnancy to critically regulate the tissue and vascular remodeling processes that establish the foundation for proper development and function of the placenta. This early role for IL-33 could impact, and possibly explain, some of the complications that arise at later stages of pregnancy in LPS-challenged rodents and in women with diverse pregnancy disorders.…”
Section: Discussioncontrasting
confidence: 47%
“…Notably, both reduced and excessive IL-33 expression have been observed in distinct pregnancy disorders, suggesting that the magnitude and/or timing of IL-33 signaling may be a critical determinant of its specific biological effects on pregnancy outcomes ( 4 , 5 , 7 , 10 13 , 15 , 16 ). Nevertheless, few studies have addressed the functional requirement for IL-33 during pregnancy progression in vivo, and these have principally focused on very late gestation in lipopolysaccharide (LPS)-challenged mice ( 17 , 18 ). Collectively, these data suggest that properly regulated IL-33 signaling may be an important feature of mammalian pregnancy and highlight the need to better understand the contributions of IL-33 to the physiological and cellular processes that underlie a healthy pregnancy.…”
mentioning
confidence: 99%
“…Invasive trophoblast cells were conspicuous in their epithelial character (e.g., expression of cytokeratins: Krt7 , Krt8 , and Krt18 ) and expression of members of the expanded prolactin (PRL) gene family ( Prl7b1 , Prl5a1 , Prl4a1 , Prl2a1 , Prl5a2 , Prl2c1 , and Prl6a1 ) ( Dataset S1 ). To date, expression of cytokeratin and a subset of PRL gene family members have formed the basis of tracking invasive trophoblast cells within the rat uterine–placental interface ( 10 , 16 21 ).…”
Section: Resultsmentioning
confidence: 99%
“…IL-33, an important early initiator of Type 2 immunity and its receptor ST2 are also enriched at the maternal fetal interface. Using IL-33-/-rats, this presence of IL-33 at the placental interface has been shown to also provide protection against LPS induced fetal restricted growth and failure of pregnancy [24]. Therefore, type 2 immunity at the maternalfoetal interface provides a significant level of protection against bacterial infection induced inflammation causing failure of pregnancy.…”
Section: Type 2 Immunity In Pregnancymentioning
confidence: 99%